Sebuah tinjauan: Meningkatkan keterampilan pendidikan bahasa inggris di Uin Mataram - Agustina, Rika Agustina (Maliki Interdisciplinary Journal, 2025)
This article discusses the improvement of the quality of English learning in the English Education Study Program of UIN Mataram. With the increasing need for English in this global era, this study program is committed to preparing students to compete at national and international levels. Therefore, UIN Mataram holds orientation activities that include TOEFL tests and introduction to IELTS. This article uses the library research method, where this article looks at how UIN Mataram implements a curriculum that combines Islamic values ​​with English learning. The results of this activity show that UIN Mataram is committed to improving the quality of education to produce graduates who are not only proficient in English but also understand the cultural and moral context.